Potential Capsule Switching from Serogroup Y to B: The Characterization of Three such Neisseria meningitidis Isolates Causing Invasive Meningococcal Disease in Canada. Issue 3 (2005) - Tsang, Raymond SW; Law, Dennis KS; Tyler, Shaun D; Stephens, Gwen S; Bigham, Mark; Zollinger, Wendell D
Abstract : Three group B Neisseria meningitidis isolates, recovered from meningococcal disease cases in Canada and typed as B:2c:P1.5, were characterized. Multilocus sequence typing showed that all three isolates were related because of an identical sequence type (ST) 573. Isolates typed as 2c:P1.5 are common in serogroup Y meningococci but rare in isolates from serogroups B or C. Although no serogroup Y isolates have been typed as ST-573, eight isolates showed five to six housekeeping gene alleles that were identical to that of ST-573. This suggested that the B:2c:P1.5 isolates may have originated from serogroup Y organisms, possibly by capsule switching.